Comparative study of outcomes between application of negative pressure wound therapy to split skin graft versus split skin graft immobilized by traditional bolster dressing - Agrawal, Naveen (International Surgery Journal, 2023)
Background: SSG is a versatile technique used for the reconstruction of wounds. The conventional techniques like traditional bolster dressing (TBD) to secure graft have been in use since the long time for the management of these wounds. NPWT is an effective advanced therapy which increase graft take by providing negative pressure to seal the space and provide persistent and uniform pressure. Methods: 60 patients were enrolled in the study. In the TBD group (30 patients) a bolster was placed on the graft which was made using a nonadherent dressing. In the NPWT group (30 patients) the SSG was secured using circumferential staples, followed by placement of VAC dressing with continuous negative pressure. Percentage of graft take assessed on 5th, 7th and 9th postop day. Results: Graft take on day 5th with NPWT group was 83.16±4.1% and in TBD group was 78.12±3.76%. On day 7th with NPWT group was 89.83±4.12% and in TBD group was 84.33±4.66%. On Day 9th with NPWT group was 96.33±5.3% and in TBD group was 92.67±5.24%. In NPWT group, mean Post SSG days were 9.9±0.61days. In TBD group, mean Post SSG days were 13.03±1.4 days. Conclusions: Our study suggest that Application of NPWT on SSG is beneficial in terms of better graft take, lesser infection, shortened post graft hospital stays and less no who needs for redo SSG and it is particularly useful anatomically challenging sites.